NILAI SOSIAL PADA IKLAN KOMERSIAL SUSU PENINGGI BADAN REMAJA DI TELEVISI - Anisa Ulfah (HUMANIS: Jurnal Ilmu-Ilmu Sosial dan Humaniora, 2021)
This study has a purpose to describe the social values ​​contained in the advertisements for body-enhancing milk for adolescents. The research was conducted using content analysis method with a qualitative descriptive approach. The source of data in this study is the documentation of commercial advertisements for body-enhancing milk aged 12-17 years, namely the Boneeto commercial version of Growing Enthusiasm, Hilo Teen version of Bintang, and Zee Platinum version 30s). Research data in the form of social value in advertising. The data collection technique is done by documentation. Based on the results of data analysis, five social values ​​were obtained, including the value of helping, the value of caring, the value of empathy, the value of belonging, and the value of cooperation. The conclusion in this research is that these social values ​​are needed by adolescents to be able to live their social life well according to the demands of society's culture in order to live side by side in harmony.